Propulsion integration design and evaluation for novel aircraft configurations - Matesanz García, Jesús (Cranfield University, 2022)
To comply with the future environmental requirements for the aviation industry, it is necessary to move towards more efficient aircraft and propulsive systems. Within this context, different novel aircraft concepts have been introduced to increase overall propulsive efficiency compared with the current technologies. A common characteristic between these concepts is the close integration of the propulsive system within the airframe. As a consequence, the impact of the propulsion integration on the aerodynamic performance of the aircraft is expected to increase in comparison with the conventional wing-mounted podded engines. However, with a few exceptions, for these new configurations the impact of the propulsion integration on the aerodynamic performance has not been sufficiently quantified. The aim of this research is to establish the methods for the aerodynamic design of the propulsion integration of the novel embedded propulsion systems. These methods are then used, for an example configuration, to quantify the impact of the propulsion integration in the overall aerodynamic performance and characteristics. A systematic design methodology was developed for the aerodynamic analysis of embedded propulsion systems. This methodology includes the parametric definition of the geometry, the aerodynamic evaluation of the propulsor, and a tailored postprocessing approach. An aft-mounted annular boundary layer ingestion propulsor for a medium-range single-aisle aircraft is used as a sample case study. A hierarchical approach with an increasing level of fidelity was applied to determine the modelling requirements for the embedded propulsion systems. This involved low order methods for drag prediction and computational fluid dynamics (CFD) methods. The CFD methods included two different fan approaches (one-dimensional and through-flow), as well as 2D axisymmetric and 3D models. To understand the limits of the design space, the design methodology was combined with a multi-objective optimisation (MOO) approach based on evolutionary algorithms. In a preliminary analysis, power savings for the whole aircraft between 3-11% were predicted due to the integration of the aft-mounted propulsor. Compared with the CFD analyses, low order models for the prediction of the aerodynamic performance found in the open literature overpredicted the power savings in approximately a 50%, making them unsuitable for the evaluation of the aerodynamic performance in embedded systems. A comparison of the modelling fidelity of the different CFD approaches shown a reduction of approximately 2% of the power savings from the original 3-11%, when 2D axisymmetric models are applied instead of more representative 3D approaches. However, the 2D axisymmetric models had about 1% of the computational cost of the 3D versions. The application of a more representative through-flow fan model also increased the predicted power savings by up to 1-1.5% when compared with a one dimensional fan. The location of the aft-mounted propulsor was found to have a significant impact on the aerodynamic performance of the embedded propulsor and the predicted power savings. Relative to the overall benefits in the power consumption of ∼ 11%, variations of approximately 4-5% on the predicted power savings are observed with the change of the propulsor axial and radial location. Locations near to the fuselage centreline are preferred. Short aft-fuselage lengths with a low fan radius of the aft mounted propulsor provided the highest thrust contribution and power savings. The more detailed design of the housing components (intake, nacelle and exhaust) of the aft-mounted propulsor has a second order impact in comparison with the propulsor location. At a fixed propulsor position, an increase of up to 1.5% of the power savings was obtained with the MOO of the aerodynamic design of the propulsion integration. From these changes, approximately one-third was obtained with the optimisation of the exhaust design, while the remaining benefits were obtained with the optimisation of the aft-fuselage, intake and nacelle geometries.
Keywords: Novel aircraft configurations; embedded propulsion; boundary layer ingestion; propulsion integration; multi-objective optimisation; computational fluid dynamics; aerodynamics